Tectonic deformation troubles in coal seems during geological exploration (2022)
In coal fields with regional stratigraphic continuity, deformed coal seams by tectonic stress, that show local structural characteristics that may be considered in the stratigraphic correlation of exploratory wells. The examples given in this paper explains if that correlation of troubles is closely related to coal average of local deformation.